2007
DOI: 10.1080/11250000600918100
|View full text |Cite
|
Sign up to set email alerts
|

The carpal gland in wild swine: Functional evaluations

Abstract: The carpal organ is a glandular complex implicated in scent communication. To investigate its ethological significance, morpho-functional evaluations were conducted on 67 glands collected from animals of different ages and sex during the 2002 hunting season (October-December) in the Bergamo district, Northern Italy. All samples were histologically and morphometrically examined to determine gland surface and thickness, number of secretory tubules per area and outer diameter of the tubules. Comparative analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…No seasonal variation is size is observed in the males as reported by Farnesi et al [72], Heise-Pavlov et al [73]. Bacchetta et al [74] reported that males had more developed and functional glands than females, with the oldest males having the highest values of gland surface, gland thickness and tubule diameter. Marking with the metacarpal glands is performed by the animal leaning forward and pawing the ground with the bottoms of its front feet this action is somewhat reminiscent of a house cat stretching forward and clawing at a carpet with its front paws.…”
Section: Each Of the Aspects Of Wild Pig Behavior Is Discussed Separasupporting
confidence: 57%
“…No seasonal variation is size is observed in the males as reported by Farnesi et al [72], Heise-Pavlov et al [73]. Bacchetta et al [74] reported that males had more developed and functional glands than females, with the oldest males having the highest values of gland surface, gland thickness and tubule diameter. Marking with the metacarpal glands is performed by the animal leaning forward and pawing the ground with the bottoms of its front feet this action is somewhat reminiscent of a house cat stretching forward and clawing at a carpet with its front paws.…”
Section: Each Of the Aspects Of Wild Pig Behavior Is Discussed Separasupporting
confidence: 57%
“…The carpal glands must be dissected out after slaughter to measure their size for study as previously reported (Bacchetta et al., 2007). However, in this study, CGDNs were counted as they are strongly and positively correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is invariable at maturity. The size of the carpal gland is affected by certain factors, such as body size and the reproductive cycle stage (Bacchetta et al., 2007), but the diverticular number remains invariable and unaffected by these factors at maturity.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of odiferous secretions, specifically androstenone from salivary glands, has been related to breeding behavior in both wild and domestic pigs (Melrose et al 1971;Estes et al 1982;Graves 1984;Dorries et al 1991). Carpal glands from wild pigs were found to be generally more robust and complex than those of domestic pigs and likely play a role in breeding activity (Hraste and Stojković 1995;Farnesi et al 1999;Heise-Pavlov et al 2005;Bacchetta et al 2007). …”
Section: Physiological Senses Driving Motivationmentioning
confidence: 99%